A elaboração do discurso no Romancero Gitano de Castelnuovo-Tedesco / Lorca - Rocha Júnior, Atilio Goltardo da [UNESP] (2015)
In the present work our aim was to reflect on some of the various extra musical and interdisciplinary procedures involved in the confection of the musical work Romancero Gitano, Mario Castelnuovo-Tedesco's authorship, with texts by Federico Garcia Lorca. To achieve this aim we have considered procedures such as rhetoric and word-painting, as well as research on biographical data about composer and poet, technical -musical analysis of each one of the movements of the work and poetical readings of the texts